Pengaruh Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Produk Fashion - Putri, Nur Fauziah; Zahrah, Halimah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The rapid development of the sneaker shoe fashion industry encourages an increase in competition between brands in attracting consumer interest, especially among students. Brand image and product quality are important factors that affect purchasing decisions. This research aims to analyze the influence of brand image and product quality on the decision to buy sneakers in students of the Faculty of Economics and Business, Muhammadiyah University of Bandung, Class of 2023. The method used is quantitative research with purposive sampling technique on 149 respondents. Data is collected through questionnaires that have been tested for validity and reliability, then analyzed using multiple linear regression. Research results show that brand image and product quality have a positive and significant effect on purchasing decisions, both partially and simultaneously, with product quality having a more dominant influence. Overall, this study concludes that strengthening Brand Image and improving product quality is an important strategy in improving the decision to buy sneakers among students.